FENOMENOLOGI: LOGOS PARTISIPATIF DAN TABERNAKEL SEMESTA (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2020)
The natural environment suffered under dominion of science, mother earth in distress and progress is no longer treated as sacrosanct. This is calling for our responsibility, and requires more serious attention from all parties, at all levels of spheres of life. In this article, I will be presented a programmatic reading of the ecological and environmental crisis from phenomenological perspective. In the first part, it will be shown that this crisis is rooted in naturalisme, i.e dualistic point of views. As a critique of this form of thoughts, a theoretical response will be demonstrated through eco-phenomenology as an interdisciplinary theory in the second part of this article, which followed by a reformulation of the concept of logos (reason) in the third part of this article based on concept logos of life from Anna-Teresa Tymieniecka and Henryk Skolimowski’s participatory mind. The fourth part is a reflection of creation as a tabernacle of the universe, a place where the divine name resides, and will be closed with a small conclusion.